2021
DOI: 10.1016/j.aninu.2021.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Calcium overload and reactive oxygen species accumulation induced by selenium deficiency promote autophagy in swine small intestine

Abstract: Selenium (Se) deficiency can seriously affect the small intestine of swine, and cause diarrhea in swine. However, the specific mechanism of Se deficiency-induced swine diarrhea has rarely been reported. Here, to explore the damage of Se deficiency on the calcium homeostasis and autophagy mechanism of swine, in vivo and in vitro models of swine intestinal Se deficiency were established. Twenty-four pure line castrated male Yorkshire pigs (45 d old, 12.50 ± 1.32 kg, 12 full-sibling pairs) were divided into 2 equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 82 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…Oxidative stress is the major cause of mitochondrial apoptosis, autophagy, and chronic inflammation, 81–84 but the crosstalk between the three is very complex, and either cooperating or antagonizing each other about cell function is possible 85 . Our study confirmed that apoptosis and autophagy acted synergistically in pro‐death and elicited increased pro‐inflammatory factors in mouse heart tissue under the same stimulation conditions (Ni exposure).…”
Section: Discussionsupporting
confidence: 70%
“…Oxidative stress is the major cause of mitochondrial apoptosis, autophagy, and chronic inflammation, 81–84 but the crosstalk between the three is very complex, and either cooperating or antagonizing each other about cell function is possible 85 . Our study confirmed that apoptosis and autophagy acted synergistically in pro‐death and elicited increased pro‐inflammatory factors in mouse heart tissue under the same stimulation conditions (Ni exposure).…”
Section: Discussionsupporting
confidence: 70%
“…Immunoblotting was carried out by blocking the membranes in 5% non-fat milk for 2 h and hatched with diluted primary antibody against GRP78, PERK, Bax, caspase-12, caspase-9, caspase-3, and Bcl-2 (Wanleibio Co., Ltd., Shenyang, China) and β-actin (1:1000, Beijing Zhong Shan-Golden Bridge Biological Technology Co., Ltd., Beijing, China) overnight [42]. Then, the members were incubated with HorseRadish Peroxidase (HRP)-conjugated immunoglobin G (IgG) (1:5000, Bioss Co., Ltd., Beijing, China).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…The specific experimental method of RT-QPCR was referred to a previous study (32). TRIzol reagent (Vazyme Biotech, China) was used to segregate total RNA from kidney tissue following the explanations supplied by the manufacturer.…”
Section: Real-time Quantitative Polymerase Chain Reaction (Rt-qpcr) Analysismentioning
confidence: 99%